Facebook Poetry and the Factors that Encourage Authors to Publish It - I Wayan Artika; Sugeng Santoso (Universitas Cokroaminoto Palopo, 2022)
The Industrial Revolution 4.0 requires all levels of life to switch to digitalization mode, including the publication of poetry. Facebook is one of the social media used by authors in publishing poetry. The purpose of this research is to analyze the existence of poetry published on Facebook and the factors that encourage the authors to publish it. The research method used is descriptive qualitative. The chosen subject is the author who publishes his poetry on Facebook, with the object characteristics and factors encourage the authors to publish it. The data will be collected with digital documentation and questionnaires and then analyzed with qualitative descriptive. Facebook poetry has several differences from poetry published in print media. In the future, this research is expected to contribute to the world of literature, especially cyber literature.